Analisis Kualitas Pelayanan Publik pada Kantor UPT Dinas Kependudukan dan Catatan Sipil di Kecamatan Bandar Laksamana Kabupaten Bengkalis - M. Dhava Fadillah Ary Saputra; Sufian Hamim (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Bandar Laksamana District is one of the implementation of public administration services. Population services include population registration and civil registration. Public services are the responsibility of the government in order to meet the basic needs of the community and to improve community welfare. The purpose of this study was to determine the quality of public services at the UPT Population and Civil Registration Office in Bandar Laksamana District, Bengkalis Regency. This study uses a qualitative descriptive method and with data collection through interviews, observations, and documentation. The data processing technique used by researchers is data analysis techniques. In this study, researchers used the Palralsuralmaln, Zeithalml, and Berry Theory which states that service quality is determined by five indicators, namely Direct Evidence (Tangibles), Reliability, Responsiveness, Assurance, and Empathy. The results of the study indicate that public services at the UPT have not been implemented properly. The service still experiences obstacles, namely limited infrastructure and facilities and limited availability of technology, lack of socialization and education to the community about services, low work culture and employee discipline, the existence of employees who have unfriendly and indifferent attitudes, and the failure to achieve the principle of public service, namely equal rights. which should not differentiate between ethnicity, race, class, gender and economic status in providing services, but UPT employees in providing services still use the principle of family.